Чувство реальности: роман / Полина Дашкова - Дашкова Полина Викторовна (Детектив-2, 2008)
Экземпляры: Ф19 (20201116) / Инвентарный номер: 60524 / Цена: 82.00 / Сис.шифр: Р2 / Авт.знак: Д 21 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6